PENEGAKAN HUKUM PEREDARAN SEPEDA MOTOR HASIL PENCURIAN OLEH KEPOLISIAN SEKTOR MANDAU - Ali Mujiono; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Problems society specially society residing in territory of jurisdiction of Polsek Mandau Sub-Province of Bengkalis is many society especially society ably middle economics downwards exploit vehicle of motorbike result of theft. Target of writing of this skripsi, first namely, Straightening Of Law Circulation Of Motorbike Result of Theft by Police Sector of Mandau, both, resistance of is Straightening of Law and third, strive to overcome execution resistance of is Straightening Of Law Circulation Of Motorbike Result of Theft.This Research type is classified in research of yuridis sosiologis, because direct writer perform a research at accurate place or location. This research is done/conducted by in Police Sector of Mandau, while and population of sampel is to represent the overall of party/ side related to problem of accurate in this research, source of data the used is primary data, data of sekunder data and of tertier, technique data collecting of research with observation, interview, bibliography study and enquette.From result of research of problem there is First, execution of[is Straightening Of Law Circulation Of Motorbike Result Of Theft By Police Sector of Mandau executed pursuant to report or denunciating of society as victim, caught by hand and also pursuant to routine Police operation which executed by each;every six-month once. But in execution, still there are some internal good resistance is Police and also society and growth of doing an injustice modus. Both, Execution resistance of is Straightening Of Law Circulation Of Motorbike Result of Theft consist of internal resistance and also resistance of eksternal. Third, effort overcome Execution resistance of is Straightening Of Law Circulation Of Motorbike Result Of Theft By Police Sector of Mandau consist of effort of preventif and also strive represif. Writer suggestion, first, make-up of amount and quality and also adequate medium support. Both, to society more koperatif to assist police duty, and more attentive in prevention to doing an injustice theft of motor vehicle and also improve sense of justice in order not to buy and exploit motor vehicle which do not equip by formal document. Third, expected by intervention of Government of Sub-Province of Bengkalis along with overall is functional of him to have a share active together Police to socialize the condition of conciousness punish and execute policy having the character of is secure and prosperous of society.